Iron chelating agents for iron overload diseases - Guido Crisponi; Valeria Marina Nurchi; Maria Antonietta Zoroddu (Thalassemia Reports, 2014)
Although iron is an essential element for life, an excessive amount may become extremely toxic both for its ability to generate reactive oxygen species, and for the lack in humans of regulatory mechanisms for iron excretion. Chelation therapy has been introduced in clinical practice in the seventies of last century to defend thalassemic patients from the effects of iron overload and, in spite of all its limitations, it has dramatically changed both life expectancy and quality of life of patients. It has to be considered that the drugs in clinical use present some disadvantages too, this makes urgent new more suitable chelating agents. The requirements of an iron chelator have been better and better defined over the years and in this paper they will be discussed in detail. As a final point the most interesting ligands studied in the last years will be presented.